TPNA10168, an Nrf-2 activator, attenuates inflammatory responses independently of Nrf2 in microglial BV-2 cells: Involvement of the extracellular-signal-regulated kinase pathway - Yasuhiko Izumi; Ai Tatsumoto; Naoko Horiuchi; Monami Arifuku; Momoko Uegomori; Toshiaki Kume; Yutaka Koyama (Elsevier, 2022)
Some chemical Nrf2 inducers possess antioxidant and anti-inflammatory properties. TPNA10168, which was identified from a chemical library as a potential activator of the Keap1-Nrf2-ARE pathway, exhibits a neuroprotective effect against oxidative stress-induced injury. However, it has not been investigated as an anti-inflammatory agent. Here we examined the effect of TPNA10168 on interferon-γ-induced proinflammatory gene expression in mouse microglial BV-2 cells. TPNA10168 significantly reduced the transcription of inflammatory genes, including TNF-α, IL-1β, IL-6, and iNOS; however, the inhibition of proinflammatory cytokine gene expression was not attenuated by inhibitors of Nrf2-regulated enzymes. Furthermore, TPNA10168 showed anti-inflammatory effects, even in Nrf2-deficient cells, and inhibited interferon-γ-induced phosphorylation of extracellular-signal-regulated kinase (ERK). Studies with an ERK pathway inhibitor demonstrated a role for ERK in the transcription of inflammatory genes. These results suggest that TPNA10168 attenuates microglial proinflammatory activation independently of Nrf2, at least in part, by suppressing interferon-γ-induced ERK signaling.